2020
DOI: 10.1071/wr19040
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying imperfect camera-trap detection probabilities: implications for density modelling

Abstract: ContextData obtained from camera traps are increasingly used to inform various population-level models. Although acknowledged, imperfect detection probabilities within camera-trap detection zones are rarely taken into account when modelling animal densities. AimsWe aimed to identify parameters influencing camera-trap detection probabilities, and quantify their relative impacts, as well as explore the downstream implications of imperfect detection probabilities on population-density modelling. MethodsWe model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
0
26
0
2
Order By: Relevance
“…For example, when using machine learning model output to design occupancy and abundance models, we can incorporate accuracy estimates that were generated when conducting model testing. The error of a machine learning model in identifying species from camera traps is similar to the problem of imperfect detection of wildlife when conducting field surveys (McIntyre, Majelantle, Slip, & Harcourt, 2020). Wildlife are often not detected when they are present (false negatives) and occasionally detected when they are absent (false positives); ecologists have developed models to effectively estimate occupancy when data have these types of errors (Guillera‐Arroita, Lahoz‐Monfort, van Rooyen, Weeks, & Tingley, 2017; Royle & Link, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when using machine learning model output to design occupancy and abundance models, we can incorporate accuracy estimates that were generated when conducting model testing. The error of a machine learning model in identifying species from camera traps is similar to the problem of imperfect detection of wildlife when conducting field surveys (McIntyre, Majelantle, Slip, & Harcourt, 2020). Wildlife are often not detected when they are present (false negatives) and occasionally detected when they are absent (false positives); ecologists have developed models to effectively estimate occupancy when data have these types of errors (Guillera‐Arroita, Lahoz‐Monfort, van Rooyen, Weeks, & Tingley, 2017; Royle & Link, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…On OGR, giraffes may find enough water in forage or access to small, non-monitored water sources, making the need to visit larger but dangerous waterholes less stringent. An alternative would be that camera traps might fail to trigger in the presence of an animal, which is sensitive to camera placement, settings and performance (Rovero et al 2013;McIntyre et al 2020), or because the photograph was of too low quality to allow for individual identification (e.g. blurry or dark images).…”
Section: Discussionmentioning
confidence: 99%
“…CT technology has enabled a tremendous leap forward for monitoring medium‐ to large‐bodied terrestrial mammals in remote areas as complex and diversified as tropical moist forests. Although species characteristics (Harmsen et al, 2010; Rowcliffe et al, 2011), abiotic factors (Noss et al, 2003) and camera‐related parameters (McIntyre et al, 2020; Moore et al, 2020; Rovero et al, 2013) have been shown to influence the detection process, the impact of the placement strategy on the detected diversity has been little studied in tropical forests. Here, we demonstrated that the CT placement had little impact on species richness and composition and provided a similar picture of the particularly rich ground‐dwelling mammal community in a tropical forest in Gabon.…”
Section: Discussionmentioning
confidence: 99%